2022
DOI: 10.1007/s10853-022-06959-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation of the Ti-5553 titanium alloy subjected to rapid heating

Abstract: The a ? b phase transformation upon heating in the Ti-5553 alloy with lamellar-nodular bimodal microstructure was tracked in situ with high energy X-ray diffraction. Rapid heating at 10, 50 and 100 °C s -1 from room temperature to 1050 °C was tested. Phase transformation on heating was studied by a combined analysis of the microstructural features that provides estimates of mass fractions, mean lattice parameters and full width at half maximum for the two phases. In comparison with equilibrium conditions, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Literature shows that Ti-5553 can be multidirectionally forged in the two-phase α + β field that consists of a microstructure with large globular and rodlike, needle-shaped α precipitates within the β phase matrix. [61][62][63]70 XRD data for Ti-5553 specimens used in this work indicate a largely β-phase alloy based on the higher intensity of the β-phase peaks relative to the α-phase ones.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Literature shows that Ti-5553 can be multidirectionally forged in the two-phase α + β field that consists of a microstructure with large globular and rodlike, needle-shaped α precipitates within the β phase matrix. [61][62][63]70 XRD data for Ti-5553 specimens used in this work indicate a largely β-phase alloy based on the higher intensity of the β-phase peaks relative to the α-phase ones.…”
Section: Discussionmentioning
confidence: 72%
“…An X-ray diffraction spectrum for a typical as-processed Ti-5553 specimen is shown in Figure . High-intensity and symmetric diffraction peaks corresponding to the β phase were present at 2θ values (deg) of 39.45 (172,771 counts, 0.52 deg fwhm), 58.54 (10,855 counts, 1.47 deg), and 72.02 (6248 counts, 2.19 deg fwhm). , The weakly intense, symmetric peak at a 2θ value of 35.45 deg (1632 counts, 0.49 deg fwhm) and asymmetric peak at a 2θ value of 85.40 deg (3254 counts, 1.33 deg fwhm) are associated with α and α″ phases, respectively. The peak assignments are based on comparison of diffraction pattern data for this alloy. ,,,, The high intensity of the peak at a 2θ of 39.45 deg indicated that the alloy has a considerable amount of β phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all conditions, there is an increase and decrease in the FWHM value. The lower FWHM values in the as-cast and 6-hour aged samples indicate that these conditions exhibit lower levels of chemical inhomogeneity and internal strain [38].…”
Section: Discussion Of the Centrifugal Casting For Orthopedic Implant...mentioning
confidence: 89%
“…[ 45,46 ] An additional cause can be modifications of the local microstructure due to the β → α phase transformation during the heat treatment. [ 47 ] All these processes can lead to complex residual stress/strain states. Further, the LPBF‐M process and the subsequent heat treatment promote the formation of high dislocation densities primarily in the β‐grain boundaries and in the α p ‐precipitates (Figure S2, Supporting Information).…”
Section: Discussionmentioning
confidence: 99%